Management of Student Empowerment: The Case Study of Improving Skills and Character Independence of Santri at Islamic Boarding School - Syafnan, Syafnan; Nikmah, Faridhatun; Anwar, Kasful; Putra, Eka; Ikhsan, Muhammad Jusuf Nur (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2024)
This study aims to determine and analyse the management of santri empowerment through Bekatren (Pesantren Economic Agency) at Pesantren Al-Anwar 3 Sarang Rembang. The empowerment intends to shape the character of santri in order to improve the skills and character of santri independence. Santri are emphasised not only to know religious knowledge, but also social knowledge, especially in the economy. This research uses descriptive-qualitative research methods. While the research model focuses on case studies. Data collection used is in-depth interviews, observation, and documentary (library content analysis). The data analysis techniques used are data condensation, data presentation and conclusion drawing. The results showed that the economic empowerment of pesantren was carried out through three business models carried out by Bekatren, namely Kopotren, AWRO water depot, and AWRE convection. The three efforts developed in the participation of the sustainability of the Pesantren Economy (Ekotren) by maximising resources, one of which is santri. Bekatren plays a role in improving the quality of human resources through sewing course training for convection, water depot business actors, and work empowerment through cooperatives. Bekatren plays a role in honing skills to form the character of independence in the entrepreneurial spirit by developing a trained attitude to be independent, honest, trustworthy, respectful of others. So that the trained attitude can shape the character of the santri.